Comparison of crypto-assets market risk proxies - Mercik, Aleksander; Cupriak, Daniel (Analiza ryzyka rynkowego na rynku kryptoaktywów. Porównanie indeksów cyfrowych aktywów, 2021)
In early 2021, the cryptoasset market capitalization exceeded $1.5 trillion, and there were more than 300 exchanges in the world where over 8,000 tokens could be traded. As part of research related to mature segments of the financial market (e.g. the stock market in the United States), scientists and practitioners have been trying to identify key risk factors for several decades, thanks to which it is possible to explain the equity risk premium for an investment in a given asset class. In recent years, there have been an increasing number of researchers trying to identify these factors for cryptoassets. The aim of this article was to analyse popular cryptoasset indices in order to identify those that can be used as a proxy of the market portfolio in order to estimate this risk factor premium. The research results indicate that the market risk factor is an important element of the market under study, and the indices that best reflect it are an index consisting of all cryptoassets weighted by capitalization and Coin100 which contains only the 100 largest cryptoassets.
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 1, s. 56-72
Keywords: cryptoassets; digital tokens; blockchain; cryptocurrency; systematic risk; CAPM; kryptoaktywa; tokeny cyfrowe; łańcuch bloków; kryptowaluta; systematyczne ryzyko; metoda wyceny aktywów kapitałowych